The Effects of Rice Bran and Blended Race Bran Oils On Indices of Coronary Heart Disease - Azlan, Azrina (2005)
Reducing dietary saturated fatty acid, increasing dietary polyunsaturated fatty acid together with the presence of naturally occurring plant minor components in fats and oil have been shown to be able to reduce plasma cholesterol level. In this study, the hypocholesterolemic effects of rice bran and blended rice bran oils were investigated. In an animal study to determine the effect of defatted and fullfat rice brans, hypercholesterolemia-induced male Sprague Dawley rats (n=77) were divided into five groups receiving diets containing; normal chow (Control), defatted rice bran diet (10% TDF; DFBC), full-fat rice bran diet (10% TDF; FRBC), cellulose diet (10% TDF; CC) and normal chow containing cholesterol (NC). All experimental diets contained 0.3% cholesterol and 0.1 % cholic acid except for the Control group. Blood samples were collected at week 3 for lipid profile determination. Results of this study showed that animals on FRBC diet had lower plasma total and LDL cholesterol levels compared to animals on DFBC and CC diets. Animals fed both DFBC and CC diets, however had higher plasma total and LDL cholesterol levels compared to the NC group. These results demonstrated that only full-fat rice bran diet caused significant reduction (pc0.05) in plasma total and LDL cholesterol. The higher content of unsaturated fatty acids (75%) and the presence of high unsaponifiable matter in the rice bran lipid fraction are suggested to contribute to the cholesterol reduction. In summary, local full-fat rice bran could be used as a good agent to reduce plasma cholesterol level. A human feeding study was carried out to determine the effects of experimental oils [palm oil (100% PO), rice bran oil (100% RBO) and blended rice bran-palm oils; 45% RBO and 60% RBO] on CHD indices of norrnocholesterolemic to mild hyper cholesterolemic subjects (n=18). The subjects received normal diets prepared using each experimental oil for 5 weeks in a single blind crossover design. In this study, diets prepared using experimental oils, did not significantly (p>0.05) alter the plasma lipid profile of subjects. However, blended oil diets (45% and 60% RBO) improved the LDUHDL ratio of subjects with 45% RBO favourable for normo- and 60% RBO favourable for mild hyper cholesterolemic subjects. Other indicators such as apo A?, apo B, Lp(a) and plasma antioxidant enzymes (glutathione reductase and glutathione peroxidase) of subjects were not affected by the dietary changes induced in the experimental oils used. The 45% RBO and 60% RBO diets also caused significant reduction ( ~ ~ 0 . 0i5n) p lasma conjugated diene and malondialdehyde levels of subjects. Plasma total antioxidant status of subjects increased following intake of blended oil diets with the highest total antioxidant status level during intake of 60% RBO diet. The increased total antioxidant status was related to significantly (pc0.05) higher level of plasma tocotrienol (5.19 ppm) compared to other diets (<2 ppm). These results demonstrated that both blended oils (45% RBO and 60% RBO) have shown some functional properties (relative to 100% RBO and 100% PO) in improving indicators of CHD. Blending of RBO and PO at specific ratios improved the fatty acid composition and antioxidant contents of the resulting oils. There could be some interactions between palm tocotrienol and rice bran oryzanol in the blended oil diets that resulted to these beneficial effects. In future, further studies are needed to determine the exact mechanisms involved.